Growth Evaluation of Marine Microalgae Chlorella sp. BDU G91771 in Calcium Rich Ossein Effluent–A Bioremediation Perspective - Kalaiselvi, B.; Jeyaleela, G. Dayana; Prathiba, K.; Ramyasri, R.; Shiyamli, S.; Vimala, S. (Asian Journal of Chemistry, 2019)
The aim of the present work is to study the growth and effluent parameters of the two ossein effluents. Growth parameters studied in this article are protein, chlorophyll, carbohydrate, moisture and the effluent parameters are alkalinity, nitrates, nitrites, ammonia, phosphates, sulphates, sulphites, calcium and magnesium. Calcium-rich effluent ossein was collected at three different clarifications stages from pioneer Jellice Industries Pvt, Ltd,, Cuddalore, which is gelatin manufacturing industry. The algae selected for the study was Chlorella vulgaris BDU G91771 which was obtained from the culture collection of National Facility for Marine Cyanobacteria (NFMC), Bharathidasan University, Tiruchirapalli, India. The culture was maintained in F/2 medium under the continuous white light at an intensity of 20 μmol photon m-2 s-1 at 25 ± 2 ºC in a controlled culture room. The chosen organisms were grown in effluent diluted with seawater (1:1, 2:2 and 3:1) amended with fertilizer grade nutrient enrichment and phosphorus sources. The untreated effluent parameters were analyzed. Chlorella vulgaris was inoculated in F/2 medium and allowed to grow in ossein effluent for 7 days. The growth of the organism was measured by calculating its culture density, dry weight, carbohydrate, protein and chlorophyll. The growth parameters of microalgae revealed that the higher content of nitrate and ammonia in HTDS effluent served as the nitrogen source and supported microbial growth.